Legislative restrictions on the exercise of corporate rights of participants of a business company within the limits of sanctions procedures - Suha , Yuliia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2026)
The article examines the legal and practical aspects of restricting the management of corporate rights of business entity participants within the framework of sanction procedures, particularly the sanctions of asset blocking and asset recovery to the state revenue. The legal nature of these sanctions under the Law of Ukraine «On Sanctions» is analyzed, as well as their impact on the exercise of corporate rights by company participants. It is established that asset blocking has a temporary character and limits the owner’s ability to dispose of property rights without depriving ownership itself. Conversely, the sanction of asset recovery to the state revenue constitutes a special form of compulsory expropriation, resulting in the termination of the sanctioned person’s corporate rights and their transfer to the ownership of the state. In such cases, the state, through an authorized body, acquires the status of a company participant and manages the corporate rights in the public interest. The High Anti-Corruption Court of Ukraine decisions are analyzed, particularly cases determining direct and indirect control over corporate structures by sanctioned individuals. It is emphasized that the lack of legislative clarity regarding indirect control risks disproportionate interference with corporate governance and the rights of bona fide shareholders. Along with this, analyzing the legal nature of the sanctions’ application, in addition to the fact that corporate rights can act as a «sanctioned» asset, the sanctions themselves can indirectly affect the exercise of corporate rights by non-sanctioned participants of business companies, which in itself will technically block the activities of the company. It is worth distinguishing between two categories of potential risks when imposing sanctions: blocking or recovery (confiscation) of corporate rights (assets) belonging to a sanctioned person; indirect influence on the exercise of corporate rights by non-sanctioned persons within the framework of sanctions imposed on the assets of another participant of the company. The author proposes improving the legislative framework to align asset recovery procedures with interest of other company shareholders, defining clear rules for the transfer of corporate rights to state management, protecting non-sanctioned participants, and ensuring proportionality of interference in property rights in line with ECHR standards.